Monetary and Exchange Rate Policies of the Euro Area : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2001)
This Selected Issues paper estimates the potential output and the associated nonaccelerating inflation rate of unemployment in the euro area. The study presents a conceptual framework for analyzing currency movements, and highlights the transmission of import price shocks on consumer prices. The paper compares different measures of trend money growth, and analyzes the monetary conditions. The study describes the stability and growth pact, outlines a simple framework for studying fiscal policy behavior, and estimates European Union countries past cyclical fiscal policy responses to output growth fluctuations.